Effect of experimental variables on coal catalytic hydrogasification in a pressurized fluidized bed. (1st January 2022) - Yan, Shuai; Qu, Xuan; Xia, Zihong; Chen, Caixia; Bi, Jicheng
Highlights: High yields of CH4 and liquid hydrocarbons were achieved in a catalytic fluidized bed. Calcium (Ca) as an additive promoted cobalt (Co) dispersion and Co-coal interaction. CaO triggered cobalt-catalyzed depolymerization of coal and hydrogenation of inert carbon. Role of temperature and pressure in catalytic hydrogasification of coal were revealed. Analyzing catalysis process and reaction kinetics to optimize coal hydrogasification. Abstract: Catalytic hydrogasification of pulverized coal was performed using a pressurized fluidized bed to investigate the effect of experimental variables including catalyst additives, temperature (600–850 °C) and hydrogen (H2 ) pressure (0.6–3.0 MPa) on the catalytic behavior of cobalt (Co) and formation profiles of target products, i.e., methane (CH4 ) and liquid hydrocarbons (HCL). The experimental results suggest that calcium (Ca) as an additive demonstrated a superior promoting effect on Co by mediating the Co-coal interaction, which initiated the catalytic depolymerization and hydrogenation of unreactive carbon. The temperature above 750 °C stimulated the diffusion of Co-Ca catalyst in the coal structure, and enhanced the coal catalytic hydrogasification by lowering the activation energy. However, the elevated temperature decreased the HCL yield due to the intensified hydrocracking. The elevation of H2 pressure strengthened the Co-Ca-Coal-H2 interaction, which conduced to the depolymerization and hydrogenation effect of Co-Ca catalyst, and improved the yield of CH4 and HCL. Based on the experimental results, a two-stage pressurized fluidized bed reactor scheme was proposed to couple the coal catalytic hydropyrolysis with char catalytic hydrogasification. Staged hydrogenation of coal was realized, and a yield of 74.2 wt% for gaseous hydrocarbons (CH4 and C2 -C3 ) and 3.36 wt% of HCL (BTX, PCX, and naphthalene) were obtained.